Epithelioid Hemangioma of the Carpus Presenting as Aneurysmal Bone Cyst - Juston Fan, DO; William H. Fang, DO, MS; Evelyn Thomas, DO; Ali Nael, MD; Mark N. Halikis, MD; Amirhossein Misaghi, MD (Journal of Hand Surgery Global Online)
Epithelioid hemangioma is a rare neoplasm characterized by locally aggressive behavior and composed of small vessels lined by epithelioid endothelial cells. Its varied presentation poses diagnostic challenges because of its ability to mimic other tumors. An 18-year-old boy presented with a painful dorsal mass on the right wrist, exhibiting features on preoperative imaging consistent with an expansile, radiolucent lesion. Initial bone biopsy suggested potential diagnoses of aneurysmal bone cysts or enchondromas. Surgical intervention, including debridement, adjuvant therapy, and bone graft, was performed. Postoperative immunohistology on intraoperative samples showed the presence of vascular markers, providing a confirmatory diagnosis of epithelioid hemangioma The patient was followed and was able to perform activities without pain for 6 months after surgery. Epithelioid hemangioma of the bone, although uncommon, demands cautious diagnosis, employing advanced techniques like immunohistochemical staining for accurate identification.